Exploration and Identification of Seed Plants (Spermatophytes) in Wana Wisata Penggaron to Develop Learning Module of Biology (Journal of Innovative Science Education, 2019)
Species richness of seed plants (Spermatophytes) at Wana Wisata Penggaron has the potential to be developed as a learning resource of biology. This study aims to develop teaching materials through exploration and identification of seed plants (Spermatophytes) in Wana Wisata Penggaron to the form of modules and knowing the validity, effectiveness of modules developed based on learning outcomes and user responses. The research method used is R & D. The results of exploration and identification of seed plants (Spermatophytes) found 64 species consisting of 3 species of Gymnosperms and 61 species of Angiosperms. Species richness of of seed plants in Wana Wisata Penggaron has represented members of the Spermatophytes division, so it can be developed as a source of learning biology. The results of the material and media expert validation were 98.44%, indicating that the modules included in the criteria were very feasible, which then the module was used in learning. The results of the module effectiveness test show that the module effectively used in learning is shown by 80% classical completeness. Affective and psychomotor learning outcomes show all students get the criteria of "Very Good". The teacher's response to module development is 94.79%, included in the criteria very feasible. Student responses were 86.8%, included in the criteria very feasible.